2013
DOI: 10.4049/jimmunol.1201391
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenoreceptor Agonist Inhibits Antigen Cross-Presentation by Dendritic Cells

Abstract: Despite widespread usage of β-adrenergic receptor (AR) agonists and antagonists in current clinical practice, our understanding of their interactions with the immune system is surprisingly sparse. Among the AR expressed by dendritic cells (DC), β2-AR can modify in vitro cytokine release upon stimulation. Because DC play a pivotal role in CD8+ T cell immune responses, we examined the effects of β2-AR stimulation on MHC class I exogenous peptide presentation and cross-presentation capacities. We demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 46 publications
3
62
0
4
Order By: Relevance
“…Based on our own data (Fig. 4A, 4B) and previous studies (14,15) showing that NE and b 2 AR agonists increase IL-10 production by LPS-DC, we examined whether b 2 ARmediated downregulation of IL-12p70 production by LPS-DC results from increased IL-10 release. Using iDC generated from IL-10 2/2 mice, we found that IL-10 deficiency does not affect b 2 AR-mediated inhibition of LPS-induced IL-12p70 production in DC (Fig.…”
Section: Idc Express Functional B 2 Armentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our own data (Fig. 4A, 4B) and previous studies (14,15) showing that NE and b 2 AR agonists increase IL-10 production by LPS-DC, we examined whether b 2 ARmediated downregulation of IL-12p70 production by LPS-DC results from increased IL-10 release. Using iDC generated from IL-10 2/2 mice, we found that IL-10 deficiency does not affect b 2 AR-mediated inhibition of LPS-induced IL-12p70 production in DC (Fig.…”
Section: Idc Express Functional B 2 Armentioning
confidence: 99%
“…It is known that stimulation of different adrenergic receptors expressed by DC modifies their migration capabilities (11), cytokine secretion (12)(13)(14), Ag uptake (15), and ability to perform cross-presentation (14). Specifically with regard to cytokine secretion, it was shown that stimulation of b 2 -adrenergic receptor (b 2 AR) modulates cytokine production by activated DC, primarily by inhibiting some proinflammatory cytokines, such as TNF-a, IL-12, and IL-6, and by increasing IL-10 and IL-33 release by these cells (13,14,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most features of the stroke-induced immunodepression may favor tolerogenic immune responses. Thus, catecholamines can inhibit the antigen-presenting capability via β2-adrenoceptors [135][136][137], corticosteroids inhibit the production of inflammatory cytokines in APCs and induce the development of tolerogenic APCs [138,139], and glucocorticoid-stimulated monocytes reduce the release of interferon-γ and IL-17 in lymphocytes, favoring the generation of Tregs [140]. IL-10 also inhibits autoimmune reactions acting on several immune cells, including APCs inducing anergic T cells that are able to suppress activation, and function of T cells in an antigen-specific manner [141].…”
Section: Sai and Brain Damagementioning
confidence: 99%
“…Действительно, у пациентов с инсультом выявляется повышенный уровень в сыворотке крови кортизола и катехоламинов, высокая концентрация которых является пре-диктором летального исхода [3,16]. Взаимодей-ствуя с β2-адренорецепторами, катехоламины подавляют антигенпрезентирующую функцию дендритных клеток и моноцитов; индуцируют толерогенные дендритные клетки, способные вызывать анергию Т-лимфоцитов и генерацию Тreg [44]. Активированные глюкокортикоидами моноциты подавляют в Т-клетках продукцию IFNγ и IL-17 и также индуцируют генерацию Тreg [126].…”
Section: системные проявления иммунного ответа на острую ишемиюunclassified